Modulation of activated macrophage immune response by Carica papaya leaf extract - Mohd Noor, Zatil Aqma (2016)
Carica papaya is a plant known for its medicinal attributes in traditional remedies. Previous usage revealed that C. papaya crude aqueous leaf extract exhibits positive effects on immune cells; increased platelet, white blood cell and neutrophil counts in dengue patients. However, the helpful effects of C. papaya crude aqueous leaf extract have not been scrutinized for possible understanding of its immune modulator activity. In this study, immune modulator activity of C. papaya crude aqueous leaf extract was tested on activated macrophage. Cytokines activities, specifically tumor necrosis factor alpha (TNF-a) was used as the indicator for immune modulator effects on the activated macrophage. The presence of the extract demonstrated decreasing amount of TNF-a detectable in cell culture supernatant. The decreased in TNF-a amount by the activated macrophage was detected by ELISA, suggesting for a reduction in TNF-a production. On the contrary, results from realtime RT-PCR did not show suppression of mRNA TNF-a expression but rather a noticeable activation of the TNF-a gene. Thus, it could be speculated that the extract did not inhibit the production of TNF-(x and subsequently its secretion. Rather, the extract could possibly interfere with the fiinctions 0f TNF-a.